Affinity-based protein profiling of MDM2 inhibitor Navtemadlin - Date,A; Wall,A; Zhang,P; Houghton,J; Lu,J; Thomas,A; Kovacic,T; Wilson,A; Tate,E; Barnard,A (Chemical Science, 2025)
Navtemadlin is a potent inhibitor of the p53-MDM2 protein–protein interaction, which plays a critical role in the proliferation of p53-wildtype tumours. Whilst Navtemadlin has progressed to multiple Phase III clinical trials in oncology, little has been disclosed regarding its selectivity for MDM2 in cells. Here, we report the synthesis and validation of photoactivatable clickable probes of Navtemadlin, and their application to de novo target discovery for Navtemadlin through affinity-based protein profiling. MDM2 was robustly identified as the main target, across two cell lines, using two distinct probe designs. While off-targets were identified, these were not consistent across cell lines and probe designs, consistent with a high degree of selectivity for the target protein. Whole proteome profiling experiments across different time points confirmed p53-mediated phenotypic activity and revealed novel expression patterns for key proteins in the p53 pathway.